VLSI-SoC : at the crossroads of emerging trends : 21st IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2013, Istanbul, Turkey, October 6-9, 2013, Revised and extended selected papers /: at the crossroads of emerging trends : 21st IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2013, Istanbul, Turkey, October 6-9, 2013, Revised and extended selected papers. (2015) - Unknown
No abstract available